Choice of a nonsteroidal anti-inflammatory drug in ankylosing spondylitis - Rimma Mikhailovna Balabanova; M. V. Podryadnova (Современная ревматология, 2014)
Ankylosing spondylitis (AS) is a chronic systemic disease with predominant axial skeleton injury, peripheral articular and entheseal involvements, and extra-skeletal manifestations. 8–10 years elapse since the first manifestations of AC to its diagnosis, leading to delays in adequate therapy, to the progression of structural and functional impairments in the axial skeleton and peripheral joints and to the development of complications. According to the international and Russia's Association of Rheumatologists guidelines, nonsteroidal anti-inflammatory drugs (NSAIDs) are an important component of AS therapy. It is necessary to carefully choose the safest NSAID for these patients, by taking into consideration that AS therapy should be long-term and continuous.The trial previously performed by the authors evaluated comorbidity in 220 AS patients long receiving nimesulide. Its long-term administration was shown to cause no increase in the level of liver enzymes. Esophagogastroduodenoscopy revealed antral gastritis in 23.6% of the patients, gastric mucosal erosions in 13, and gastric ulcer disease without an exacerbation in 3.6%. It was noted that the physicians had not prescribed gastroprotectors to the patients. Nimesulide caused no blood pressure (BP) elevation even in patients who had baseline hypertension. Elevated BP occurred in 2.5% of the patients. There was no clear association of higher BP with nimesulide intake since the patients had previously used other NSAIDs, mainly diclofenac, to treat severe pain syndrome. These findings suggest that in addition to its analgesic activity, nimesulide shows good tolerability in patients with AS, which permits its long-term use, but in this case the gastrointestinal tract and BD should be carefully monitored, which will be able to prevent the possible adverse events characteristic of the entire group of NSAIDs.